Implantação da ferramenta OEE (eficiência global do equipamento) na linha de pintura em uma indústria metalúrgica - Desiombra, Juliano (2014)
This study aimed to evaluate the process to implement an OEE (overall equipment efficiency) in a large metalurgical company. This work was developed using literature, exploratory, quantitative, qualitative, action research and documentation. The development of this research describes the steps to deploy the tool OEE from a bibliography research, the development of the equations to calculate losses, availability and efficiency. The time of deployment tool OEE were five days. In a first moment the area and equipment were studied. TPM theories were studied by the members of the project, and afterwords the OEE tool implementation actions were taken. This study also looked for discuss the losses indicators and their causes . It was possible to notice that OEE is an effective tool to improve equipment performance.